Adult patients with pulmonary arterial hypertension due to congenital heart disease: a review on advanced medical treatment with bosentan - Schuuring, Mark J (Dove Medical Press, 2010)
Pulmonary arterial hypertension (PAH) is a progressive disease with poor survival outcome. PAH is classified by the 2009 updated clinical classification of pulmonary hypertension and a major subgroup is PAH due to congenital heart disease (CHD) with systemic-to-pulmonary shunt. CHD-PAH is a result of systemic-to-pulmonary shunting and chronic increased flow that ultimately results in adaptations of pulmonary vasculature and endothelial dysfunction. The advanced stage is called Eisenmenger syndrome which forms a small percentage (1%) of all CHD patients. Therapies targeted on PAH symptoms are called primary therapy for PAH, but most CHD-PAH patients progress to advanced therapy which is directed at the PAH itself. In CHD-PAH, advanced therapies are extensively investigated for all three major pathways: endothelin-1 receptor antagonists such as bosentan, prostanoids such as epoprostenol and phosphodiesterase 5 inhibitors such as sildenafil. Endpoints in most trials were catheterization hemodynamics, World Health Organization functional class, six-minute walking distance and patient-focused outcomes, based on quality of life questionnaires and Borg dyspnea index. The BREATHE-5 and EARLY study were two important randomized controlled trials showing efficacy of bosentan at short follow-up. Moreover in patients with Eisenmenger syndrome, one recent survival retrospective study with majority of patients on bosentan showed strong survival benefit over conservative therapy. A diversity of prospective cohort and retrospective studies were performed but all with limited data, due to small numbers and heterogeneity of underlying CHD diagnoses. Further larger studies are needed to determine optimal treatment for adults with CHD-PAH. This review focuses on bosentan in CHD-PAH. In particular, we discuss outcome of various clinical trials and compare efficacy and safety of bosentan to other advanced therapies.